Testing liquidity constraints in 10 Asian developing countries: an error-correction model approach - Habibullah, Muzafar Shah; Smith, Peter; Wan Ngah, Wan Azman Saini (2006)
An error-correction model is used to estimate the fraction of consumers who are liquidity-constrained in 10 Asian developing countries. Our estimates of the fraction of consumers who are liquidity-constrained range between 0.25 and 0.98. We further investigate whether financial liberalization has resulted in the reduction of liquidity constraints in these countries. However, the results find support for this only in the cases of South Korea, Sri Lanka and Taiwan.